KANDUNGAN ZAT BESI SMOOTHIE PISANG AMBON DENGAN PENAMBAHAN KACANG MERAH - Sunarto Sunarto; Adriyani Adam; Hijrah Asikin; Suriani Rauf; Winda Saputri (Media Gizi Pangan, 2022)
ABSTRACT Smoothies are made from fruit and vegetables. The manufacture of smoothie products does not only rely on making produsts that are nutritious but also acceptable to the publicin terms of taste, aroma, texture, and color. The addition of red beans was chosen because in general people only know red beans for processed vegetables, while red beans are high in protein and iron. The purpose of this study was to determine the iron content of Ambon banana smoothie with the addition of red beans. This study is a preexperimental study with a post test design group desaign,comparing Ambon banana smoothie with the addition of 15% red beans with Ambon banana smoothie with the addition of 20% red beans. The results of the research on Ambon banana smoothie with the addition of red beans formula X2 has a higher iron content is 101.71 mg, while formula X1 is 86.22 mg. it is recommended for futher researchers to analyze the protein content of Ambon banana smoothie with the addition of red beans. Keywords: Smoothie, Ambon Banana, Red  Beans, Iron Levels